2021
DOI: 10.3390/ijerph18179349
|View full text |Cite
|
Sign up to set email alerts
|

The Increase in Frequency of Protective Behavior against Pesticide Poisoning in Narail, Bangladesh through Use of an Easy Paper Checklist; an Interventional Study

Abstract: Protecting the health of farmworkers is a crucial issue. Previous studies report that safety training and educational interventions might increase farmworkers’ protective behaviors. The present study aimed to investigate the effectiveness of distributing a checklist as an interventional measure for pesticide protection in rural Asia, where pesticide poisoning is a major problem. This study was a community-based interventional study, using the distribution of a checklist with pesticide protective habits in Nara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…The weak intervention group did not show improvements in hypertension, diabetes, and risk behavior. This result is in contrast with that of a previous intervention study, without a control group, where the use of a checklist poster for pesticide protective behavior significantly changed the behavior among farmers in the region [ 26 ]. This finding indicates the need for more frequent and elaborate interventions than the weak intervention to improve blood pressure and risk behavior related to NCDs.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The weak intervention group did not show improvements in hypertension, diabetes, and risk behavior. This result is in contrast with that of a previous intervention study, without a control group, where the use of a checklist poster for pesticide protective behavior significantly changed the behavior among farmers in the region [ 26 ]. This finding indicates the need for more frequent and elaborate interventions than the weak intervention to improve blood pressure and risk behavior related to NCDs.…”
Section: Discussioncontrasting
confidence: 92%
“…All interventions were conducted in the local language. We selected the interventions from previous interventional research on NCDs, namely checklist poster [ 26 ], seminar and video interventions [ 7 10 ], and texts messages [ 20 ]. We experienced the project that easy paper checklist about pesticide protective behavior improved outcome in this area [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with the very high-risk and high-risk groups were high age, female gender, and shorter educational years. A previous interventional study that used an educational checklist for pesticide protection in Bangladesh showed that the effect of educational intervention was smaller in groups consisting of individuals who were older and had shorter educational years [ 29 ]. The proportions of aging individuals, females, and those with short education years in the very high-risk and high-risk groups were quite high.…”
Section: Discussionmentioning
confidence: 99%